Web-Based Village Public Service Information System in Nambangan Selogiri Village Wonogiri - Fahriza Wahyu Akbar; Wijiyanto Wijiyanto; Hanifah Permatasari (Politeknik Negeri Lhokseumawe, 2026)
Digital transformation at the village government level has become a crucial aspect of realizing efficient, transparent, and responsive public services. However, Nambangan Village currently faces administrative bottlenecks due to its reliance on a conventional service system. The process of issuing various certificates, such as the Certificate of Inability (SKTM), domicile letters, and cover letters, requires residents to physically visit the village hall. This practice leads to crowded queues, potential errors in population data recording, and low time efficiency in service delivery. This study aims to design and develop a web-based Village Public Service Information System that adapts to the operational needs of both village officials and the community of Nambangan Village. The system development method applied is the Software Development Life Cycle (SDLC) using the Waterfall model, which encompasses the stages of requirements analysis, system design, implementation, testing, and maintenance. The system is built using PHP, HTML, CSS, and JavaScript programming languages, supported by a MySQL database for integrated data management. The primary features implemented include online document submission, population data management, service tracking for village officials, public village information delivery, and a public grievance reporting system. Software quality assurance was functionally evaluated through the Black Box Testing method. The final outcome of this research is expected to provide an applicable technological solution for Nambangan Village to optimize public administrative governance and provide accessible services for the community without spatial or temporal constraints.